Polymorphisms in platelet glycoproteins Ia and IIIa are associated with arterial thrombosis and carotid atherosclerosis in type 2 diabetes - Pellitero, Silvia; Reverter, Jordi L.; Tàssies, Dolors; Pizarro, Eduarda; Monteagudo, Juan; Salinas, Isabel; Aguilera, Eva; Sanmartí, Anna; Reverter, Juan Carlos (Thrombosis and Haemostasis, 2010)
To determine the genotype distributions of the polymorphisms in platelet glycoproteins (GP) Ib-alpha, Ia/IIa and IIb/IIIa and their association with clinical arterial thrombosis and preclinical carotid atherosclerosis in type 2 diabetes we studied 229 patients with type 2 diabetes and 229 controls matched by age, gender and ethnicity. Biochemical and haemostasis analyses were performed. The GP Ib-alpha VNTR, GP Ia 807 C/T and GP IIIa Pl(A) polymorphisms were determined by PCR. Thrombotic events were registered and carotid atherosclerosis was evaluated by ultrasound examination. A total of 107 patients had clinical atherothrombosis (CA), 65 subclinical atherosclerosis (SA), and 57 had no evidence of atherosclerosis (NA). There were no differences in allele frequencies and the genotype distribution of platelet GP polymorphisms between diabetic patients and controls. The VNTR Ib-alpha polymorphism was not associated with CA. We found a significant association between CA and the 807T (odds ratio [OR]: 2.86, confidence interval [CI]: 1.65–4.93; p<0.001) and PlA2 (OR: 2.03, CI: 1.13–3.65; p=0.03) alleles (in GP Ia and GP IIIa, respectively) in comparison to SA and NA group. Diabetic patients with the coexistence of the 807T and PlA2 alleles presented the highest risk of CA (OR: 3.59, CI: 1.64–7.8; p<0.001). The coexistence of both 807T and PlA2 alleles was also associated with the presence of SA (OR: 9.00, CI: 1.10–73.42; p=0.04). In conclusion, the 807T allele of GP Ia and the PlA2 allele of GP IIIa, and specially its combination, may confer an additional risk for development of carotid atherosclerosis and arterial thrombosis in type 2 diabetes.
Keywords: Arterial thrombosis; carotid atherosclerosis; platelet glycoprotein; polymorphism; type 2 diabetes